The future of Indian aviation from the perspective of environment-centric regulations and policies. Issue 4 (December 2020) - Rathore, Himanshu; Nandi, Shirsendu; Jakhar, Suresh Kumar
Abstract: The Indian aviation industry has grown by over 20% annually in the past two years. It is likely to grow at a double digit growth rate in the coming decade. The stupendous rise in its economic activity has raked up concerns about its environmental impact. India has signed up for Carbon Offset and Reduction Scheme for International Aviation (CORSIA) in 2016, which is to be mandated from 2026. This article discerns the possible implications that such an environmental policy can have on the Indian aviation sector by modelling the impact of a prospective carbon tax on the domestic aviation sector.